PENGARUH MEDIA KARTU HURUF TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN DI POS PAUD MEKAR SARI DISTRICT TAPUNG - Hanud Rusnayati; Jaspar Jas; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims 1) To determine the ability to recognize letters in children aged 4-5 years prior to the application of the letter in the post card media ECD Mekar Sari subdistrict Tapung. 2) To determine the ability to recognize letters in children aged 4-5 years after the implementation of the letter in the post card media ECD Mekar Sari subdistrict Tapung. 3) To determine how much influence the media card application letter to the ability to recognize letters in Pos Paud Mekar Sari District Tapung. This type of research is an experimental research. Samples of research that children aged 4-5 years in Pos Paud Mekar Sari District Tapung consisting of 14 children, consisting of 7 men and 7 women. Collecting data using observation and documentation. Based on the survey results revealed that 1) The ability to recognize letters in Children Aged 4-5 Years in Pos Paud Mekar Sari District Tapung before treatment is given in the form of media cards belonging letters began to grow, meaning that a new child to know some letters and can not recognize letters well. 2) The ability to recognize letters in Pos Paud Mekar Sari District Tapung after treatment is given in the form of letters increased media card and classified evolve as expected, meaning that children are able to recognize the letters are taught by a teacher and be able to distinguish the letters designated by the teacher. 3) The effect of the application of the card media letter to the ability to know the letters in Childhood 4-5 Years in Pos Paud Mekar Sari District Tapung that is equal to 51.55%, which means that children are able to recognize the letters well after applying the letter card media.